An analysis of embedded weak discontinuity approaches for the finite element modelling of heterogeneous materials. (December 2022) - Ortega, A.; Roubin, E.; Malecot, Y.; Daudeville, L.
Highlights: The use of the Embedded Finite Element Method (E-FEM) to simulate local material heterogeneities is analyzed in detail. A new fully consistent weak discontinuity enhancement function is proposed. Basic simulations are used to compare the classical approach, commonly used in literature, and the new fully consistent approach proposed in the paper. A discussion evaluates both model performance and ease of implementation. Abstract: This paper analyses in detail the use of the Embedded Finite Element Method (E-FEM) to simulate local material heterogeneities. The work starts by a short review on the evolution of weak discontinuity models within the E-FEM framework to discuss how they account for the presence of multiple materials within a single element structure. A theoretical basis is introduced through some mathematical weak discontinuity definitions and the Hu-Washizu variational principle, for then establishing a set of requirements for retaining variational and kinematic consistency for any weak discontinuity enhancement proposal. From a general definition of a displacement enhancement field, two particular enhancement functions are derived by considering different consistency requirements: one which has been typically used in previous works and other which truly possesses variational consistency. A discussion is held on enhancement stability properties and the impact to global finite element solution processes. In the end, numerical simulations are made to assess the performance of each of these enhancements on the task of modelling a classical bi-material layered 3D tension problem and a more realistic heterogeneous sample having spherical inclusions of different radii. The final discussion evaluates both model performance and ease of implementation.